New coalition formation game for spectrum sharing in cognitive radio networks. (20th October 2014) - Hamouda, Soumaya; El‐Bessi, Sourour; Tabbane, Sami
SUMMARY: In cognitive radio networks, Secondary Users (SUs) can access the spectrum simultaneously with the Primary Users (PUs) in underlay mode. In this case, interference caused to the licensed users has to be effectively controlled. The SUs have to make spectrum access decisions in order to enhance their quality of service, but without causing harmful interference to the coexisting PUs. In this paper, we propose a cooperative spectrum decision, which enables the SUs to share the spectrum with the PUs more efficiently. Our approach is based on a new coalitional game in which the coalition value is a function of the SUs' spectral efficiencies, the inter‐SUs interference, and the interference caused to the PUs. By applying new Enter and Leave rules, we obtain a stable coalition structure. Simulation results show that the SUs' spectral efficiencies are considerably increased and that the interference caused to the coexisting PU is reduced by about 7.5% as compared to an opportunistic spectrum access scheme. Moreover, the proposed coalitional game results in a more balanced spectrum sharing in the network. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : In this paper, we proposed an efficient spectrum access scheme in cognitive radio networks based on a new coalition formation game. Thanks to the proposed coalition value as well as the coalition formation rules, the different secondary users cooperate to form coalitions around every primary user and share the spectrum with him without causing harmful interference in the network. We show that the interference level in the network is considerably lessened and that the spectrum sharing is more balanced.